The Analysing of the Emotional Intelligence Scores of the Special Education Teacher Candidates for the Predictor of Multiple Intelligences Areas - Tugba Pursun* (European Journal of Educational Research, 2019)
This study aims to analyse the emotional intelligence scores of the special education teacher candidates for the predictor of multiple intelligences areas. This study was conducted through relational scanning model. 211 teacher candidates, 106 females and 105 males, participated in the study. Data were collected through Personal Information Form, Teele Multiple Intelligence Inventory and Schutte Emotional Intelligence Scale. Logistic regression analysis was used to find whether the gender and grade level variables, and optimism, utilization of emotions and the scores of emotion evaluation are statistically significant in defining predominant intelligence areas or not. SPSS 24.0 was used in the data analysis process. The results revealed that while the gender variable and optimism scores are significant variables predicting the determination of individuals in which predominant intelligence is both interpersonal and not, optimism and evaluation of emotions scores are significant variables predicting the determination of individuals whose predominant intelligence is both visual and not. However, the results suggested that demographic variables (gender and grade level) and emotional intelligence scores did not affect kinesthetic, musical, intrapersonal, logical and verbal intelligence areas which were found as the predominant intelligence areas of teachers.